Exploring The Position and Role of Arabic in Indonesian Society: A Descriptive Analysis - Fauzie Muhammad Shidiq; M. Syihabul Ihsan Al-Haqiqy; Muhammad Triwibowo; Syaiful Mustofa (Universitas Islam Negeri Palangka Raya, 2023)
Many other researchers have made the contribution of Arabic to human life. However, more attention should be paid to the position and role of Arabic in society. Language is an effective medium of communication. Arabic certainly has many contributions that cannot be avoided from human life. This research aims to discover Arabic's position and role in Indonesian society. This research uses descriptive qualitative methods with data collection techniques of observation, documentation, and interviews. The results of this study indicate that (1) the position of Arabic in Indonesian society has broad benefits, namely as a source of knowledge, as a strengthening of daily worship, and as moral formation. (2) The role of Arabic in Indonesian society has a contribution, namely as a language of international communication, as a source of absorption language for Indonesians, and as a language of diplomacy (economic, political, and cultural). This research implies that we can further explore the position of the Arabic language, which has an important role and position in human life. This research implies that we can comprehensively know more details about the role and position of Arabic to provide wider information to the Indonesian people.